THE TECHNIQUES AND ACCURACY IN THE TRANSLATION OF CULTURAL WORDS IN GEORGE ORWELL’S ANIMAL FARM - Vina Saphagus Tieas; Eko Budi Setiawan; Dwi Aji Prajoko (Humaniora Scientia, 2017)
This study aimed to analyze the techniques employed to translate the cultural words and their accuracies. The data was obtained from a classic novel written by George Orwell entitled Animal Farm and its Indonesian version under the same title translated by Bakdi Soemanto. This research applied descriptive-qualitative method. As the population of this  research was too large, this research applied purposive sampling. The techniques  employed in translating the cultural words were  judged  by  using  translational  equivalent  method.  While,  the  degree  of accuracy  was  determined  by  the  employment  of  distribusional  method.  The finding  of  this  research  presented  ten  techniques  employed  to  translate  the cultural words, namely adaptation (15), amplification (7), borrowing (14), calque (7), description (11), generalization (11),  modulation (2), particularization (3), reduction (4), and transposition (6). In terms of  accuracy, the renderings were classified into three degrees. They were accurate (47),  less accurate (30), and inaccurate (3). Most of the cultural words were translated accurately and only a small number of the words was translated inaccurately.   Keywords: Cultural Words, Translation Techniques, Accuracy in Translation